2017
DOI: 10.18203/2320-1770.ijrcog20173473
|View full text |Cite
|
Sign up to set email alerts
|

The study of maternal and fetal outcome in pregnant women with thyroid disorders

Abstract: Background: Thyroid disorders are among the common endocrine disorders in pregnant women after diabetes mellitus. Several changes are observed in maternal thyroid function during pregnancy and failure to adapt to these physiological changes results in thyroid dysfunction. It is well established that not only overt, but subclinical thyroid dysfunction also has adverse effect on mother and the fetus, like miscarriages, preterm delivery, preeclampsia, eclampsia, polihydromnios, placental abruption, post-partum ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Various adverse effects such as miscarriage, preeclampsia, anemia, low birth weight, preterm birth, increased maternal and fetal morbidity, and mortality is reported. 7 The prevalence of hypothyroidism during pregnancy is estimated to be 0.3-0.5 % for overt hypothyroidism and 2-3 % for subclinical hypothyroidism. 8 Obstetrics and Gynaecology Department of Kathmandu Medical College Public Limited, Sinamangal, Nepal, from March 2020 to August 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Various adverse effects such as miscarriage, preeclampsia, anemia, low birth weight, preterm birth, increased maternal and fetal morbidity, and mortality is reported. 7 The prevalence of hypothyroidism during pregnancy is estimated to be 0.3-0.5 % for overt hypothyroidism and 2-3 % for subclinical hypothyroidism. 8 Obstetrics and Gynaecology Department of Kathmandu Medical College Public Limited, Sinamangal, Nepal, from March 2020 to August 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The increased cases of anaemia with COVID 19 can be because COVID 19 pandemic resulted in limitations in availability of antenatal care and inadequate iron and folic acid supplementation which added on to the pre-existing burden of nutritional anaemia in India. Studies conducted pertaining to the incidence of anemia and GDM with thyroid disorders such as by Gupta et al 13 , Sahu et al 14 and Sreelatha S et al 15 showed increased incidence of these conditions in patients with thyroid dysfunction. 16 .…”
Section: Discussionmentioning
confidence: 99%
“…4 It is now well established that not only overt, but also subclinical thyroid dysfunction has significant adverse effects on pregnancy and fetal development. 5 Uncontrolled thyroid dysfunctions can be associated with adverse pregnancy outcomes like miscarriage, placental abruption, pre-eclampsia, preterm delivery etc. 6 preterm birth, low birth weight, increase admission to neonatal intensive care and increase perinatal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%